PENGARUH MOTIVASI, DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. HASIL RAYA INDUSTRIES - Sunardi; Robi Wijaya (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
This study aims to determine The Influence of Motivation, Discipline and Job Satisfaction on Employee Performance PT. Hasil Raya Industries. This study uses SPSS software analysis tool version 18 windows, and shows the result that Motivation, Discipline, and Job Satisfaction partially and simultaneously have an influence on Employee Performance PT. Hasil Raya Industries. The method used in this study is with quantitative approach where the data obtained through 76 respondents who are samples are processed using statistical tools, then presented in the form of scientific analysis. After performing data collection either through questionnaire and field observation, using multiple linear regression analysis where the regression analysis F count = 241,917, because F count > F table (241,917> 1,993), this means that motivation, discipline and job satisfaction have a significant influence on employee performance. Motivation variables partially affect the employee performance where the value of partial correlation of 0.925 with a value of t arithmetic 20.895> 1.993 t table. Partial Discipline variables affect the employee performance where the partial correlation value of 0.931 with a value of t arithmetic 22.027> 1.993 t table. With this result variable Discipline has the greatest influence when compared with variable motivation and job satisfaction. Job Satisfaction Variables in partial effect on employee performance where the value of partial correlation of 0.913 with a value of t arithmetic 19.271>1.993 t table.